2023
DOI: 10.3389/fonc.2023.997776
|View full text |Cite
|
Sign up to set email alerts
|

Increases prognostic value of clinical-pathological nomogram in patients with esophageal squamous cell carcinoma

Abstract: BackgroundThis study was intended to construct a brand new prognostic nomogram after combine clinical and pathological characteristics to increases prognostic value in patients with esophageal squamous cell carcinoma.MethodsA total of 1,634 patients were included. Subsequently, the tumor tissues of all patients were prepared into tissue microarrays. AIPATHWELL software was employed to explore tissue microarrays and calculate the tumor-stroma ratio. X-tile was adopted to find the optimal cut-off value. Univaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Recently, there has been an increasing trend to develop nomogram for cancer prognosis, primarily because of their userfriendly graphical interfaces enabling visualization of the prognostic strength of various relevant factors (29,30). Compared with the traditional TNM system, the advantage of nomogram is its ability to incorporate a wide array of prognostic indicators to formulate a noninvasive tool that could predict the prognosis according to an individual patient's profile (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been an increasing trend to develop nomogram for cancer prognosis, primarily because of their userfriendly graphical interfaces enabling visualization of the prognostic strength of various relevant factors (29,30). Compared with the traditional TNM system, the advantage of nomogram is its ability to incorporate a wide array of prognostic indicators to formulate a noninvasive tool that could predict the prognosis according to an individual patient's profile (31,32).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, utilizing our tissue microarray (TMA) cohort from Zhongshan Hospital, which encompassed 205 LUAD patients, we conducted immunohistochemistry staining for UPP1. The expression of UPP1 in tumor cells was then analyzed using the AI-based software, Aipathwell 25,26 . Our data indicated that elevated UPP1 expression was inversely correlated with both overall survival (OS) and recurrencefree survival (RFS) among LUAD patients (Fig.…”
Section: Tumor Cells and The Association Of Upp1 With Patient Prognosismentioning
confidence: 99%
“…Slides were scanned using Pannoramic MIDI (3DHISTECH, Hungary). For the quantification of IHC images, we used the AI-based IHC scoring software, Aipathwell, developed by Servicebio (Wuhan, China) 25,26 . This software generated four metrics: Positive Area (%), Mean Density, Area Density, and H-score (Supplementary Data 5).…”
Section: Immunohistochemistrymentioning
confidence: 99%